Behind the Scenes with Data at the IMF : An IEO Evaluation. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2016)
This report examines whether the IMF has effectively leveraged an important asset: data. It finds that in general, the IMF has been able to rely on a large amount of data of acceptable quality, and that data provision from member countries has improved markedly over time. Nonetheless, problems with data or data practices have, at times, adversely affected the IMF's surveillance and lending activities. The roots of data problems are diverse, ranging from problems due to member countries' capacity constraints or reluctance to share sensitive data to internal issues such as lack of appropriate staff incentives, institutional rigidities, and long-standing work practices. Efforts to tackle these problems are piecemeal, the report finds, without a clear comprehensive strategy that recognizes data as an institutional strategic asset, not just a consumption good for economists. The report makes a number of recommendations that could promote greater progress in this regard.